PSYCHOLOGICAL TRENDS IN THE TREATMENT OF PTSD - Griffiths, Gareth (E-Journal VFU, 2024)
This paper explores the evolution of PTSD management, encompassing its historical background, evidence-based therapies, and the latest advancements. The study examines various therapeutic approaches and technological integrations, individual strategies, challenges, ethical considerations, and future directions, providing insight into current practices and potential advancements in the field.